Comprehensive characterization of viral integrations and genomic aberrations in HBV‐infected intrahepatic cholangiocarcinomas. Issue 4 (5th December 2021) - An, Jihyun; Kim, Deokhoon; Oh, Bora; Oh, Yoo‐Jin; Song, Jihyun; Park, Naomi; Kim, Ha Il; Kang, Hyo Jeong; Oh, Ji‐Hye; Kim, Wonkyung; Lee, Eunjung; Sung, Chang Ohk; et al.
Abstract: Background and Aims: Despite the epidemiological association between intrahepatic cholangiocarcinoma (iCCA) and HBV infection, little is known about the relevant oncogenic effects. We sought to identify the landscape and mechanism of HBV integration, along with the genomic architecture of HBV‐infected iCCA (HBV‐iCCA) tumors. Approach and Results: We profiled a cohort of 108 HBV‐iCCAs using whole‐genome sequencing, deep sequencing, and RNA sequencing, together with preconstructed data sets of HBV‐infected HCC (HBV‐HCC; n = 167) and combined hepatocellular cholangiocarcinoma (HBV‐cHCC/CCA; n = 59), and conventional ( n = 154) and fluke‐related iCCAs ( n = 16). Platforms based on primary iCCA cell lines to evaluate the functional effects of chimeric transcripts were also used. We found that HBV had inserted at multiple sites in the iCCA genomes in 45 (41.7%) of the tumors. Recurrent viral integration breakpoints were found at nine different sites. The most common insertional hotspot (7 tumors) was in the TERT (telomerase reverse transcriptase) promoter, where insertions and mutations (11 tumors) were mutually exclusive, and were accompanied by promoter hyperactivity. Recurrent HBV integration events (5 tumors) were also detected in FAT2 (FAT atypical cadherin 2), and were associated with enrichment of epithelial–mesenchymal transition–related genes. A distinctive intergenic insertion (chr9p21.3), between DMRTA1 (DMRT like family A1) and LINC01239 (long intergenic non‐protein coding RNA 1239), had oncogenic effects through activation of the mammalian target of rapamycin (mTOR)/4EBP/S6K pathway. Regarding the mutational profiles of primary liver cancers, the overall landscape of HBV‐iCCA was closer to that of nonviral conventional iCCA, than to HBV‐HCC and HBV‐cHCC/CCA. Conclusions: Our findings provide insight into the behavior of iCCAs driven by various pathogenic mechanisms involving HBV integration events and associated genomic aberrations. This knowledge should be of use in managing HBV carriers.